Dilated Cardiomyopathy in Behcet's Disease in a Young Male Patient - Khederlou, Hamid; Taheri, Samin; Sadeghi, Alireza; Moghtader Mojdehi, Amirhossein (International Journal of Cardiovascular Practice, 2017)
Behcet?s disease is a multisystemic, inflammatory and chronic disorder characterized by recurrent oral aphthous ulcers and genital ulcers, uveitis and other manifestations, including systemic organ involvement. Cardiac involvement in Behcet?s disease is rarely however, it plays an important role in prognosis and increases mortality. We hereby have reported a case of Behcet's disease with dilated cardiomyopathy. He was presented with constitutional symptoms and also oral and genital aphthous ulcers, pseudofolliculitis, tachycardia, arthritis, splenomegaly, ESR (erythrocyte sedimentation rate) and CRP (C-reactive protein) elevation and LV systolic dysfunction with LVEF=45% were found in evaluation. He was started on Azathioprine and Prednisolone.